Extraction of a foreign body due to a penetrating wound in the buttock region by a firearm ultrasound-guided: a case report - Huerta-Velázquez, Jose Miguel; Jimenez-Curiel, Alexa (International Surgery Journal, 2023)
The use of ultrasound as a diagnostic and therapeutic support method for patients with penetrating gunshot wounds must be individualized in patients who require the removal of the foreign body. We report the case of a male in the fourth decade of life with a penetrating wound in the gluteal region on the left side of approximately 0.5 cm by 0.5 cm. Initially, stabilization was performed according to ATLS and later the patient was left in charge of general surgery. Doppler ultrasound was performed as the first and only imaging study to assess a possible vascular condition, which was negative. Due to the location of the projectile added to the medical-legal need of the patient to obtain the projectile, it was extracted with the help of an ultrasound-guided radiologist without the need to make an incision, since the bullet was extracted through the entrance hole. The reported literature mentions that there are key points, mentioned later in this article, for the extraction of bullets by firearm. Evidence for the use of ultrasound is limited but it should be kept in mind that ultrasound can be a useful diagnostic and therapeutic tool in removal of foreign bodies.